2014
DOI: 10.1108/ijchm-01-2013-0051
|View full text |Cite
|
Sign up to set email alerts
|

Understanding CSR from the perspective of Chinese diners: the case of McDonald’s

Abstract: Purpose – The study aims to explore the expectations and perceptions of corporate social responsibility (CSR) strategies among Chinese fast-food diners, and to investigate the relationships among CSR strategies, consumer satisfaction and customer loyalty behaviors. Chinese diners’ knowledge about a real world brand’s CSR activities was also investigated. Design/methodology/approach – Setting the research context on the fast food industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 39 publications
0
39
1
1
Order By: Relevance
“…Other studies showed that the correlation is indirectly positive, through other mediating variables such as the whole evaluation of service, the word of mouth, the purchase intentions and the satisfaction level (Salmones, Perez, & Del Bosque, 2009;Mandhachitara and Poolthong, 2011;Choi and La, 2013;Chomvilailuk & Butcher, 2014;Shin & Thai, 2015). The results of this study indeed contradict with other studies that found insignificant correlation between CSR and CL (Xu, 2014;Moisescu, 2015b). This might be due to cultural differences and lack of general awareness of CSR importance to society.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…Other studies showed that the correlation is indirectly positive, through other mediating variables such as the whole evaluation of service, the word of mouth, the purchase intentions and the satisfaction level (Salmones, Perez, & Del Bosque, 2009;Mandhachitara and Poolthong, 2011;Choi and La, 2013;Chomvilailuk & Butcher, 2014;Shin & Thai, 2015). The results of this study indeed contradict with other studies that found insignificant correlation between CSR and CL (Xu, 2014;Moisescu, 2015b). This might be due to cultural differences and lack of general awareness of CSR importance to society.…”
Section: Resultscontrasting
confidence: 97%
“…Nevertheless, the study revealed that there is a need for full and transparent disclosure of CSR policies and activities, adopting more customer-centric approach, where customers are the center of attention, ensuring the fairness and adequacy of prices, and improving quality. Xu (2014) examined the relationship between CSR and CL in the fast food industry in China, precisely within the customers of McDonald's, by measuring five important aspects; consumer's dine-out behavior, expectations of CSR, perception of CSR, loyalty to and satisfaction of McDonald's customers and the demographics of the respondents. Xu found that the fast food diners in China emphasized on two particular activities of CSR, which are the human well-being and providing safe healthy/safe food, while other CSR activities were less important to customers.…”
Section: Csr and CLmentioning
confidence: 99%
“…Research should fundamentally debate the relevance and application of sustainability to the sector and its relationship with external stakeholders and move away from narrow focuses. More specifically, "one size does not fit all" with regards to sustainability and CSR, hence societies and organisations with different cultures and beliefs may be motivated to be involved in sustainability and CSR developments for different reasons and may also face diverse barriers to implementation (Nyahunzvi, 2013;Thompson et al, 2018;Wells et al, 2015;Wells et al, 2016b;Xu, 2014;Yadav et al, 2016). Hence, the goal of this special issue was to encourage new theoretical and empirical development on sustainability and CSR studies in the hospitality and tourism field.…”
Section: Introductionmentioning
confidence: 99%
“…The fast-food industry in Hong Kong is the product of "McDonalisation" as it is in many Asian countries (Xu, 2014;Ritzer, 2011) [81] [66]. Various similar food concepts such as coffee café culture and pizza and sandwich cultures have invaded Asia in the last few years (Xu, 2014;Lan and Khan, 1995) [81] [45].…”
Section: Introductionmentioning
confidence: 99%
“…Various similar food concepts such as coffee café culture and pizza and sandwich cultures have invaded Asia in the last few years (Xu, 2014;Lan and Khan, 1995) [81] [45]. As the concept gained acceptance by the customers at large, competition began to increase during the recovery of the economy in 1998 (Hong Kong Food Market Trends, 2007) [29].…”
Section: Introductionmentioning
confidence: 99%